منهج السلفية المعاصرين في العقيدة - Mohammed 'Abdulhameed Sleibi,; Abdull Rahman Mahmood,; Indriaty Ismail,; Zul'azmi Yaakob, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Salafi has emerged as a new school of thought in the modern era. They are alleged to be propagating the Muslims of returning to the belief of the so-called salaf al-salih (the pious of the past) from the Prophet’s Companions and their successors in the matter of `aqidah using method that claimed to be true compared to methods used by other Islam’s school of thoughts. However, their claim for the use of such method has been objected by the ulama of Ahl Sunnah wa al-Jamaah. As the method used by this group in understanding the teachings of Islam has negative impact on the Muslim society, an objective study in recognising the method of this new school of thought is needed in warranting the extent of its compatibility with the method of the Salaf ulama. Hence, this study will employ deductive method in assembling ideas and statements made by contemporary Salafi ulama. These ideas will be analysed critically and then compared to the ulama Ahl Sunnah wa al-Jamaah’s views. The result of the study shows that the Salafi method has its root from the 3rd Hijrah school of thought. It also shows that the method is in contrast with the method of the Ahl Sunnah wa al-Jamaah as explicated by the Muslim ulama. The dissemination of this school of thought among the Muslim society has raised distorted understanding and conflict among Muslim youth especially with regard to furu` (the branch of religion) issues related to discourse in `aqidah.